Happiness among Traditional Fisher Families: Moral Economy, Psychological Resilience, and Religious Faith in Coastal North Sumatra, Indonesia - Zakiyussyarif, Muhammad; Sahrul , Sahrul (TEMALI : Jurnal Pembangunan Sosial, 2026)
This study examines how traditional fisher families in Dahari Indah Village, Talawi Subdistrict, Batu Bara Regency, North Sumatra, understand and produce happiness amid the structural economic uncertainty of the fisheries sector. Departing from a critique of welfare approaches that reduce happiness to material indicators, this research argues that fisher family happiness cannot be understood linearly as a function of income stability. Instead, it emerges from a complex configuration of economic adaptation, family relational dynamics, and religious faith. The study employs a qualitative phenomenological approach, involving ten fisher families through field observation and in-depth interviews. The findings show that income fluctuations resulting from limited fishing equipment and environmental conditions are perceived as part of the rhythm of everyday life rather than as crises that automatically negate happiness. Families instead produce happiness through practices of economic simplicity in household management, supportive family relationships, and the ability to interpret life pressures through patience, acceptance, and gratitude. Religious practices—such as daily prayers, Quranic study gatherings, and supplication—function as everyday routines that regulate emotions, reduce anxiety, and cultivate inner calm amid economic uncertainty, while simultaneously strengthening psychological resilience and the stability of domestic relationships. Theoretically, these findings demonstrate that happiness in coastal communities constitutes a relational, contextual, and religious practice of everyday life. This study enriches the understanding of happiness as an ethical-spiritual condition, resonating with Al-Farabi’s concept of sa‘ādah and aligning with the psychological well-being perspective, which emphasizes self-acceptance, positive relationships, and meaningful life orientation under structural constraints. Practically, this article underscores the importance of coastal development policies that extend beyond income enhancement to include family strengthening, mental health support, and community-based religious practices.